TMOD-42. PROSPECTIVE VALIDATION OF AN EX VIVO 3D ASSAY FOR PREDICTION OF TEMOZOLOMIDE RESPONSE IN GLIOBLASTOMA. (11th November 2019) - Smith, Ashley; Holmes, Lillia; Shuford, Stephen; Kanos, Charles; Gardner, Stephen; Hodge, Philip; Lynn, Michael; Edenfield, Jeff; DesRochers, Teresa
Abstract: Standard treatment for newly diagnosed glioblastoma (GBM) is surgical resection followed by radiation with concurrent temozolomide (TMZ). For those who do not respond there are few clinical options, survival is low, and there no biomarkers to direct the decision of second-line treatment. We have developed a 3D cell culture assay to predict response to TMZ and 11 other potential therapies for GBM. Our assay uses GBM tissue obtained at surgical resection and the test's 7-day turnaround maximizes clinical actionability of results. We performed a small, prospective study examining the ability of the assay to predict response to TMZ. Ten newly diagnosed GBM patients were enrolled over 12 months. Two patients were removed due to refusal of treatment, and three failed the assay (3/8, 62.5% success). The remaining five patients received radiation and concurrent TMZ following surgical resection. Using progression-free survival (PFS) measured from the completion of radiation therapy and setting 4 months as the cutoff for response, we were able to determine the ability of our assay to predict TMZ response. The assay correctly predicted all five patients (100%). The average PFS for the two predicted responders was 8 months compared to the three predicted non-responders at 3 months, p = 0.0634. In this limited dataset, MGMT methylation did not appear to play a role as two of three predicted non-responders were methylated along with one of two predicted responders. Average overall survival of the predicted TMZ responders was 13 months compared to 6 months for the predicted non-responders, p = 0.0634. This early data indicates the potential for this assay to inform clinicians of the best course of action for their patients. Further enrollment of patients into the 3D-PREDICT clinical trial will provide a larger dataset for better validation of the predictive value of this new assay.